INTERNAL AND EXTERNAL FACTORS INFLUENCING PRE-SERVICE TEACHERS IDENTITY CONSTRUCTION - Elisabeth Wulan Wahyuningtyas (UC Journal: ELT, Linguistics and Literature Journal, 2020)
This paper explored internal and external factors that could influence pre-service English teacher in doing teaching in the classroom. The study aimed to investigate how pre-service teachers constructed their identity in order to prepare themselves to be teachers in true education field. However, it might help them to reflect themselves to be able to understand their identity as teacher candidates. Furthermore, interview would be conducted to get further and deep information from the participants and also to clarify their responses. Therefore, it encouraged the writer to conduct a qualitative study about pre-service English teacher identity.